Bioaccessibility and public health risk of heavy Metal(loid)s in the airborne particulate matter of four cities in northern China. (August 2021) - Ren, Yuxuan; Luo, Qing; Zhuo, Shaojie; Hu, Yuanan; Shen, Guofeng; Cheng, Hefa; Tao, Shu
Abstract: Atmospheric coarse particulate matter (PM10 ) enriched with heavy metal(loid)s could pose potentially significant health risk to humans, while accurate health risk assessment calls for characterization of their bioaccessibility, besides the total contents. The health risk of major toxic heavy metal(loid)s in the PM10 from four large cities in northern China via inhalation was investigated based on their total contents and bioaccessibility. The annual mean concentrations of PM-bound Zn, As, Pb, and Mn in the atmosphere of the four cities were 650, 305, 227, and 177 ng⋅m −3, respectively. The levels of heavy metal(loid)s in the PM10 were generally higher in winter but lower in summer in all four cities, which resulted primarily from the emissions associated with coal combustion for district and household heating and the unfavorable meteorological conditions in winter. The bioaccessibility of heavy metal(loid)s in the PM10 ranged from 0.9 to 48.7%, following the general order of Mn > Co > Ni > Cd > Cu > As > Cr > Zn > Pb. Based on their total contents in the PM10, most heavy metal(loid)s posed significant public health risk via inhalation exposure in the four cities. However, after accounting for the bioaccessibility of metal(loid)s, the non-carcinogenic risk of most metal(loid)s was negligible, except for As in the PM10 of Jinzhong, while only the carcinogenic risk posed by Cr and As in the PM10 exceeded the acceptable level. These findings demonstrate the importance of characterizing the bioaccessibility of airborne PM-bound heavy metal(loid)s in health risk assessment and could guide the on-going efforts on reducing the public health risk of PM10 in northern China. Graphical abstract: Image 1 Highlights: Contents and bioaccessibility of metal(loid)s in PM10 from four cities were analyzed. Zn, As, Pb, and Mn had much higher abundance than the other metal(loid)s in the PM10 . The bioaccessibility of heavy metal(loid)s in the PM10 varied largely (0.9–48.7%). Health risk would be over-estimated based on total contents of metal(loid)s in PM10 . PM-bound As posed the most significant public health risk via inhalation exposure.